Śrī Nabakṛsṇa Caudhurī : eka jībanī - Dāsa, Cittarañjana (Inṣṭiṭuṭ aph Orieṇṭāla eṇḍ Oriśāna Ṣṭaḍij, Di Ẏunibharsa, 1992)
On the life and work of Nabakr̥shṇa Caudhurī, 1901-1984, Indian freedom fighter, reformer, and statesman from Orissa